Market Dynamics and Investor Perceptions After the Acquisition of Shares by GoTo Directors: A Case Study of the Impact of Management Attitudes on Market Sentiment and Stock Performance - Eri Mardiani; Maiza Fikri; Atika Atika (West Science Business and Management, 2023)
This research explores the intricate relationship between management attitudes, investor perceptions, market sentiment, and stock performance within the context of GoTo directors' share acquisitions. Using a case study approach, interviews with key stakeholders and surveys of retail and institutional investors were conducted to gather primary data. The results reveal a complex interplay of factors: management attitudes driving acquisitions, mixed investor perceptions, short-term market dynamics influenced by behavioral biases, and limited long-term effects on stock performance. These findings emphasize the importance of transparency in corporate governance and the need for communication strategies that address investor concerns. While share acquisitions can generate short-term market reactions, long-term stock performance is influenced by broader economic and industry-specific factors. The study contributes to our understanding of corporate governance and investor relations dynamics and their implications for both investors and corporate leaders.